INDUSTRIAL MEDICINE: EXPERIENCE AND PROBLEMS - I S Ivashova; A V Vanin; D A Moiseenko (Клиническая практика, 2017)
The article discusses the positive experience of the Southern regional medical center of FMBA of Russia in the system of industrial healthcare. Describes the experience of work in selected areas of industrial medicine - diving and marine medicine, the tasks and the experience of the Center of professional pathology, discussed a number of problematic issues.